2012
DOI: 10.1002/jbm.a.34254
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma loaded in situ‐formed hydrogel enhances hyaline cartilage regeneration by CB1 upregulation

Abstract: The efficacy of three‐dimensional (3D) culture on the proliferation and maturation of chondrocytes seeded into a hydrogel scaffold was assessed. Three types of hydrogel were prepared for the 3D culture of primary isolated chondrocytes. Chondrocyte proliferation was assessed using a live/dead viability/cytotoxicity assay and semiquantitative RT‐PCR after 3D culture in hydrogel. Cylindrical defects in the center of rat xyphoids were used for the implantation of platelet‐rich plasma (PRP)/hydrogel composites. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Previous studies showed that the mesenchymal stem cells (MSC) exhibited higher level of chondrogenic marker expression after the PRCR treatment of cells inside the scaffold environment compared to the 2D culture 21. Even mature chondrocyte when was seeded in the 3D systems showed high viability and efficacy in the proliferation and expression of chondrogenic gene markers after the treatment with PRCR 22. Another study showed opposite results, as the treatment of the ligament fibroblasts with high doses of PRCR in the scaffold culture system showed negative responses in terms of cells function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the mesenchymal stem cells (MSC) exhibited higher level of chondrogenic marker expression after the PRCR treatment of cells inside the scaffold environment compared to the 2D culture 21. Even mature chondrocyte when was seeded in the 3D systems showed high viability and efficacy in the proliferation and expression of chondrogenic gene markers after the treatment with PRCR 22. Another study showed opposite results, as the treatment of the ligament fibroblasts with high doses of PRCR in the scaffold culture system showed negative responses in terms of cells function.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo results demonstrated that PRP–GPT hydrogels could improve cartilage remodelling by upregulating SOX‐9, CB2, ChM‐1 and aggrecan after a 7 day incubation period. We have also attempted to regenerate non‐articular cartilage by the implantation of xyphoid chondrocytes encapsulated in PRP–GPT hydrogels (Lee et al ., ). A xyphoid defect rat model was used to show that the PRP–GPT hydrogels can induce proliferation and differentiation of chondrocytes in vitro and in vivo by inducing elevated levels of ChM‐1 and CB1.…”
Section: Potential Biomedical Applicationsmentioning
confidence: 97%
“…These results show that PRP had differential effects on chondrocytes; that is, promoting the synthesis of hyaline cartilage matrix while cellular progression to terminal hypertrophy is not facilitated or at least delayed. Another study further demonstrated that the chondrogenic differentiation and maturation induced by PRP treatment was related to the up-regulated expression of cannabinoid receptor 1 and 2 [36,37]. However, a few authors have argued that PRP treatment was unable to induce the deposition of typical cartilage matrix components [32,34], that there was no difference in the enhancement of extracellular matrix (ECM) production between the groups with PRP, PPP, whole blood or fibrin glue added into gelatin-based microcarriers [38], and that PRP treatment could in fact induce a dedifferentiation of chondrocytes towards a fibroblast-like phenotype [33].…”
Section: Effect Of Platelet-rich Plasma On Cellsmentioning
confidence: 99%